THE EFFECT OF USING ROLE-PLAYING TO IMPROVE SPEAKING SKILLS IN THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL SUNAN KALIJAGA - kiki megawati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Speaking is therefore a means of communicating with others in order to share information and obtain new information from others. The purpose of this study was to determine the effect of using a role-playing strategy in SMP Sunan Kalijaga Malang. This study used a quasi-experimental design and the population of this study was 20 students of SMP Sunan Kalijaga Malang. The researcher analyzed the data using the independent T-test, test from the results of the students' post-test scores to be able to know the final results whether or not there was an influence on the use of role-playing strategies. The results of the study found a significance level of 0.00 < from 0.05. This shows that students who are taught using role-playing strategies and students who are taught using conventional differ significantly in speaking skills.keywords:Â Speaking skill, Role playing, effect